Training and delivery of a novel fatigue intervention: a qualitative study of rheumatology healthcare professionals' experiences. Issue 2 (27th August 2019) - Dures, Emma; Rooke, Clive; Hammond, Alison; Hewlett, Sarah
Abstract: Objectives: Successful, non-pharmacological research interventions are challenging to implement in clinical practice. The aim of the study was to understand the experiences of rheumatology nurses and occupational therapists (tutors) delivering a novel fatigue intervention in a trial setting, and their views on requirements for clinical implementation. After training, tutors delivered courses of a manualised group cognitive-behavioural intervention to patients with rheumatoid arthritis in a 7-centre RCT (RAFT, Reducing Arthritis Fatigue by clinical Teams using cognitive-behavioural approaches), which demonstrated reduced fatigue impact for two years. Methods: 14 tutors participated in interviews and eight tutors also participated in a focus group. Data were audio-recorded, transcribed and analysed using inductive thematic analysis. Results: five main themes were identified. 'Exciting but daunting' reflected the mixture of excitement and anxiety in intervention training and delivery. 'Skills practice and demonstrations were essential' captured the value of learning and practicing together, even though the process could be uncomfortable. 'An individual approach to a standardised intervention' showed how tutors negotiated adherence to the manual with delivery using their own words. 'Becoming a better practitioner' describes how participation enhanced tutors' wider clinical practice. 'Pragmatic and flexible' highlights practical adaptations to facilitate training and intervention roll out. Conclusion: These insights inform strategies for clinical implementation of an evidence-based intervention that addresses a patient priority, with implications for other successful research interventions. Tutors believed the skills acquired during RAFT enhanced their wider clinical practice, which highlights the benefits of upskilling members of clinical teams to provide self-management support to patients.